Effect of Hydrogen on Superelasticity of the Titanium Nickelide-Based Alloy; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Lotkov A. Aleksandr; Baturin A. A. Anatoly Anatolievich; Grishkov V. Victor; Rodionov I. Ivan; Kudiyarov V. N. Victor Nikolaevich; Lider A. M. Andrey Markovich (2015, 2015)
Title screen